New Insight into the Molecular Drug Target of Diabetic Nephropathy - Vivian Soetikno; Wawaimuli Arozal; Melva Louisa; Rianto Setiabudy (International Journal of Endocrinology)
Diabetic nephropathy (DN) lowered quality of life and shortened life expectancy amongst those affected. Evidence indicates interaction between advanced glycation end products (AGEs), activated protein kinase C (PKC) and angiotensin II exacerbate the progression of DN. Inhibitors of angiotensin-converting enzyme (ACEIs), renin angiotensin aldosterone system (RAAS), AGEs, and PKC have been tested for slowing down the progression of DN. The exact molecular drug targets that lead to the amelioration of renal injury in DN are not well understood. This review summarizes the potential therapeutic targets, based on putative mechanism in the progression of the disease.